Renewable Energy - Economic Growth Nexus in South Africa: Linear, Nonlinear or Non-existent? - Nyoni, Bothwell; Phiri, Andrew (International Journal of Energy Economics and Policy, 2020)
With escalating fears of climate change reaching irreversible levels, much emphasis has been recently placed on shifting to renewable sources of energy in supporting future economic livelihood. Focusing on South Africa, as Africa’s largest energy consumer and producer, our study investigates the short-run and long-run effects of renewable energy on economic growth using linear and nonlinear autoregressive distributive lag (ARDL) models. Working with data availability, our empirical analysis is carried out over the period of 1991 to 2016, and our results unanimously fail to confirm any linear or nonlinear cointegration effects of the consumption and production of renewable energy on South African economic growth. We view the absence of cointergation relations as an indication of inefficient usage of renewable energy in supporting sustainable growth in South Africa and hence advise policymakers to accelerate the establishment of necessary renewable infrastructure in supporting future energy requirements. Keywords: Renewable energy; economic growth; ARDL; nonlinear ARDL; South Africa; Sub-Sahara Africa (SSA). JEL Classifications: C13; C32; C52; Q43 DOI: https://doi.org/10.32479/ijeep.7706